The Development of an Early Diagnostic Method for Alzheimer’s Disease - Yulia K. Styufliaeva; Andrew A. Zelinsky; Oksana A. Malikova; Aleksandr A. Rubel (Proceedings)
Alzheimer’s disease (AD) is the most common form of dementia, characterized by neuronal degeneration and death [...]